Thinking Actively in Social and Context Flipped Classroom Learning in Physics of Work and Energy to Improve Students' Critical Thinking, Self-Efficacy and Character Compassion - Hadijah, Siti; Sarwi, Sarwi; Susilawati, Susilawati; Masturi, Masturi (JIPF (Jurnal Ilmu Pendidikan Fisika), 2024)
This study aims to understand, describe, analyze, and measure the increase of critical thinking skills, self-efficacy and the character compassion due to the application of the flipped classroom online learning model equipped by thinking actively in social and context (TASC). This work is quasi-experimental research using the quantitative analysis. Data was collected from several techniques, consist of observation, tests, non-test and documentation.  The validity of the data in this study used normality and homogeneity tests, and hypothesis testing using t-test.  The results show that the critical thinking ability obtained t-count value 1.988 with a significance 0.052, that means the average critical thinking ability of the experimental group is higher than that of control group.  Then, the self-efficacy component, a t-count value of 1.843 was obtained with a significance of 0.068, which means that the average self-efficacy ability of the experimental group is higher than that of the control group.  The t-count value of the character compassion component is 1.910 with a significance of 0.058, which means that the average of character compassion ability of the experimental group is higher than to that of the control group.  The results of the study showed that the TASC flipped classroom online learning model in physics of work and energy matter can improve critical thinking skills, self-efficacy and character compassion of the students on senior high school.